2021
DOI: 10.3389/fvets.2021.615405
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Differential Expression Profiling of Pulmonary circRNAs Associated With Immune Reaction to Pasteurella multocida in Goats

Abstract: Pasteurella multocida is a highly versatile pathogen that infects a wide range of animals, including goats, causing pneumonia and hemorrhagic septicemia. Circular RNA (circRNA) is a type of non-coding RNA that plays an important role in regulating cellular metabolism. However, whether and how circRNA is involved in regulating immune responses in the goat lung has not been reported. Thus, this study was designed to examine the function of circRNA in goats infected with Pasteurella multocida. Goats were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Wu and coworkers established a P. multocida -induced pneumonia mouse model and transcriptome sequencing showed that the expression of the IL-17 gene was significantly upregulated in the lungs of P. multocida -infected mice ( Wu et al, 2017 ). In our previous study, transcriptome sequencing and small RNA sequencing on goats challenged with P. multocida identified 2,673 significantly differentially expressed mRNAs and 56 miRNAs, some of them are involved in inflammatory response, immune effector process, and cell activation in response to endogenous stimuli ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wu and coworkers established a P. multocida -induced pneumonia mouse model and transcriptome sequencing showed that the expression of the IL-17 gene was significantly upregulated in the lungs of P. multocida -infected mice ( Wu et al, 2017 ). In our previous study, transcriptome sequencing and small RNA sequencing on goats challenged with P. multocida identified 2,673 significantly differentially expressed mRNAs and 56 miRNAs, some of them are involved in inflammatory response, immune effector process, and cell activation in response to endogenous stimuli ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to explore the pathogenic mechanisms of serotype D Pm–infected Hainan black goats. A previous study reported that Pm–challenged goats showed changes at the transcriptome level in the goat lung [ 10 ]. Therefore, this study explored the effects of different infection periods on the miRNA and mRNA levels of goats.…”
Section: Discussionmentioning
confidence: 99%
“…cp037861). Pm HN01 isolates were revived for the current study as described previously [ 10 ]. Briefly, the bacteria were confirmed by a 16s rRNA polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These virulence factors participate in the processes of bacterial growth, colonization, host infection, and cell damage. As the main components of the bacterium, the capsule and LPS play important roles in the pathogenesis of P. multocida [ 5 ]. For example, the virulence of P. multocida capsule mutants in mice was weak [ 5 ]; in the UDP-galactose (galE) mutant of P. multocida , LPS biosynthesis was thoroughly weakened in mice [ 6 ]; the virulence of different serotypes of P. multocida capsule mutants substantially decreased in mice [ 6 ].…”
Section: Introductionmentioning
confidence: 99%